1979
DOI: 10.3758/bf03198789
|View full text |Cite|
|
Sign up to set email alerts
|

The independence of dynamic spatial orientation from luminance and refractive error

Abstract: The effect of refractive error and luminance on circularvection, the illusory sensation of self-motion resulting from rotation of the visual field, was determined. Neither reduction of luminance to levels near absolute scotopic threshold nor induced refractive errors of more than 16 diopters abolished circularvection or influenced any of its latency measures. The results are discussed in terms of the role of the peripheral visual field and the nature of the visual stimulus in ego orientation.A growing body of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

1982
1982
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(47 citation statements)
references
References 23 publications
(22 reference statements)
3
43
0
1
Order By: Relevance
“…The distance between the subject's eyes and the screens of the monitors was 25 em. Leibowitz, Rodemer, and Dichgans (1979) have shown that vection is independent of the refractive error. Consequently, the small distance between the monitors and the subject's eyes should not have had an effect on the perceived vection.…”
Section: Apparatusmentioning
confidence: 99%
“…The distance between the subject's eyes and the screens of the monitors was 25 em. Leibowitz, Rodemer, and Dichgans (1979) have shown that vection is independent of the refractive error. Consequently, the small distance between the monitors and the subject's eyes should not have had an effect on the perceived vection.…”
Section: Apparatusmentioning
confidence: 99%
“…Scotopic!Ambient System Reports of experiments with other aspects of egocentric localization and orientation have indicated major control by the peripheral visual field (Brandt, Dichgans, & Koenig, 1973;Dichgans & Brandt, 1974;Trevarthen, 1968), insensitivity to the accommodative stimulus (Leibowitz, Rodemer, & Dichgans, 1979), at most a low level of sensitivity to change in stimulus intensity (Leibowitz et al, 1979), and control by large visual fields (Dichgans & Brandt, 1974;Trevarthen, 1968). This has led to the suggestion (Leibowitz, Post, Brandt, & Dichgans, 1982;Trevarthen, 1968) that visual processing of localization and orientation is under control of an "ambient" system, whereas the processing of fine detail and form is under control of a "focal" system, whose main control is by more central (i.e., foveal and near foveal) pro-cesses, involves perception of fine detail, and is sensitive to the accommodative stimulus.…”
Section: Adaptation Ofvpel Within Amentioning
confidence: 99%
“…As documented, features of aging that contribute to the use of conservative strategies during obstacle crossing by older adults include the deterioration of muscle strength and vision (Chou et al, 2003;Leibowitz et al, 1979;Brandt et al, 1986). In order to reduce the risks of tripping and falling, older adults decrease crossing speed, decrease crossing step length, and increase the step width over the obstacle (Chen et al, 1991).…”
Section: Success Ratementioning
confidence: 99%